PERANCANGAN SISTEM INFORMASI PENCATATAN PEMBAYARAN SPP BKB PAUD MENUR 13 BERBASIS WEB - Rahma Melanie (2020)
Nowadays, technology becomes one of the important factor to support human activities. It helps many sector in daily basis. Having a system in education brings a significant impact towards the business processes. BKB Paud Menur 13 for example, for student registration fee and tuition fee, still use manual book to process and record the transaction information. On this thesis, the writer tries to develop an application system website based that can be used for administrative activities in BKB Paud Menur 13. In addition, the idea of this application will use HTML and PHP as the basis access, waterfall as a method and MySQL for the database. The design of application will easy use and user friendly for the interface and the process flow. The presence of this application hopefully will bring significant impact for students and school as the organizations. For students and parents this app will help them to trace their tuition fee records meanwhile for the school it will help to collect the data for payment reports. The writer aware that the implementation of the payment system in BKB Paud Menur 13 will become a new transformation to support administrative activities. The last but not least, the system will bring efficiency and effectiveness in terms of time, places, reduce risk and reduce other expenses in the future due to the data information is no longer recorded manually using the paper book, but now it well organized and maintained in the database system.